2006
DOI: 10.1186/1471-2407-6-283
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes released by EBV-infected nasopharyngeal carcinoma cells convey the viral Latent Membrane Protein 1 and the immunomodulatory protein galectin 9

Abstract: Background: Nasopharyngeal carcinomas (NPC) are consistently associated with the Epstein-Barr virus (EBV). Their malignant epithelial cells contain the viral genome and express several antigenic viral proteins. However, the mechanisms of immune escape in NPCs are still poorly understood. EBV-transformed Bcells have been reported to release exosomes carrying the EBV-encoded latent membrane protein 1 (LMP1) which has T-cell inhibitory activity. Although this report suggested that NPC cells could also produce exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
210
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(221 citation statements)
references
References 38 publications
10
210
0
1
Order By: Relevance
“…All cells were maintained at 37°C with 5% CO 2 . The C15 xenograft tumor was cultured in vitro for 2 d as previously described (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All cells were maintained at 37°C with 5% CO 2 . The C15 xenograft tumor was cultured in vitro for 2 d as previously described (12).…”
Section: Methodsmentioning
confidence: 99%
“…Exosomes are a recently discovered mechanism through which cancer cells and virally infected cells can manipulate their microenvironment. Viruses can use the exosome pathway for virus egress and immune evasion (11)(12)(13). Interestingly, EBV-infected cells release exosomes containing LMP1 that induce T-cell anergy (14).…”
mentioning
confidence: 99%
“…There are still many puzzles of ovarian cancer, including the relationship between the tumor and the host immune system, and the mechanisms of the development, invasion and metastasis of the tumor. Exosomes are a kind of microvesicles released by many types of cells such as tumor cell (1)(2)(3)(4), antigen presenting cells (APC) (5,6) and epithelial cells (7,8). Recent research revealed that exosomes purified from the ascites of patient with ovarian cancer contain some immunological-effect molecules (9).…”
Section: Introductionmentioning
confidence: 99%
“…Latency type II, on the other hand, results in the expression of LMP1, LMP2 and EBNA1 as seen in HL and NPC, whereas in latency type III, all latent proteins/antigens are expressed in the course of acquired immune deficiency syndrome (AIDS)-related lymphomas and lymphoblastoid cell lines (LCLs) [17,18]. Of note, the LMPs-carrying exosomes have been previously shown to be secreted by EBV-infected cells particularly the NPC cells [19][20][21].…”
Section: Exosomal Latent Membrane Proteins (Lmps)mentioning
confidence: 99%